Career Development of Lower Social Class Adolescents in South Korea. (October 2019) - Hwang, Mae Hyang; Lee, Jihye; Jung, Ae-Kyung
Despite increased efforts and a broadened understanding of social class and its impact on career development, the career development of lower social class adolescents and its interaction with sociocontextual factors remain understudied. The current study explored the educational and career experiences of South Korean high school seniors using a qualitative approach and the gender and social class career development model. Our sample included 14 lower class high school seniors who were preparing for different career paths after graduation. The data were collected at three time points, through two semistructured interviews, documents, and brief phone-call surveys. An inductive thematic analysis of 28 semistructured interviews and documentations revealed three domains with seven themes. The results demonstrated an influence of lower social class on adolescents' socialization, access to resources, affectional and academic barriers, and academic and career attainment. The implications of the results for career counseling, interventions, policies, and future research are discussed.